FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU HIDUP BERSIH DAN SEHAT UNTUK MENCEGAH COVID-19 PADA SISWA SISWI SD NEGERI SRIMULYO 4 KECAMATAN GONDANG KABUPATEN SRAGEN - Ambarwati, Retno; Kristiningtyas, Y. Wahyunti; Wijayanti, Maria Tri (Akademi Keperawatan Giri Satria Husada Wonogiri, 2021)
Background: The widespread spread of Corona Virus Disease (COVID-19) in Indonesia resulted in various prevention efforts being encouraged. The focus of prevention efforts is to break the chain of spread of the COVID-19 virus. Some effective ways that can be done are social distancing, self-isolation, and the application of Clean and Healthy Living Behavior (CHLB). As CHLB has often been socialized by the Ministry of health through various programs and activities. Several effective measures can be taken to prevent the spread of COVID-19. In addition to social distancing and self-isolation, the application of CHLB is also able to minimize the possibility of exposure to viruses. Clean and healthy living behavior that can be applied by getting used to washing hands, every before and after activities. Hand washing is done on running water and by using soap. It can also be done with alcohol-based hand sanitizer, which acts as a disinfectant. Objective: Know the factors that affect clean and healthy living behavior to prevent covid-19. Method : Type of analytical survey research with cross sectional approach. The research population is students of SD Negeri Srimulyo 4 grade IV to VI as many as 134. The number of samples of 59 students with purposive sampling techniques. Closed questionnaire research instruments. Analyze univariate and bivariate data with spearman rank correlation formula. Result: No influence of CHLB knowledge on CHLB behavior (P value = 0.801), no influence of parental support on CHLB Behavior (p value = 0.082), no influence of knowledge about covid-19 on phbs behavior (p value = 0.043), there is an influence of school support on phbs behavior (p value = 0.039) and there is an influence of attitude to phbs behavior (p value = 0.002). Conclusion: Factors that significantly influence CHLB behavior are knowledge of covid-19, school support and attitudes. While CHLB knowledge and parental support have no effect on CHLB behavior.